Sehat Dalam Perspektif Al-Qur'an - Miskahuddin, Miskahuddin (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2020)
Al-Qur'an as a noble holy book and a guide for human life, always guides people to be positive for their own good, including talking about the importance of maintaining health for the freshness and fitness of the human body both physically and mentally. Healthy in the positive sense described in the Koran, namely the preservation of all the potential gifts of God on him in the form of organs that can functionally move various work activities to build himself and the environment in which he lives and is. There is a specificity that can be described by the Koran on the physical and mental health aspects of this matter, especially all the potential for body and soul to always be meaningful to be healthy and strong to perform worship to Allah SWT perfectly as proof of his gratitude to Allah SWT who created it with a hope to get the pleasure of Him and get the highest mau'nah from God to get heaven jannatun na'im. Syurga jannatun na'im longs for strong people to worship and do good deeds perfectly according to the will and wishes of Allah SWT or those who are pleased by Him. Of course, only people who are healthy and strong, physically and mentally, as well as whose perfection in worshiping or doing good deeds to Allah will occupy a quality heaven. Strong is synonymous with being physically and mentally healthy, therefore only those who are strong and healthy will also be able to carry out God's mandate, namely religion with the perfection of all its Shari'a. Therefore people who want to get happiness and prosperity accompanied by safety in the world and in the hereafter are obliged to strive to be healthy physically and mentally and always respect, maintain and glorify physically and spiritually so that they are always healthy or get used to living healthy within the framework of Islamic law guided by teachings of al-Qur'anul Karim and Al-Hadith. Â